\(\left(x+2\right)\left(x^2-2x+4\right)-x\left(x-3\right)\left(x+3\right)=26\)
\(\Leftrightarrow x^3+8-x\left(x^2-9\right)=26\)
\(\Leftrightarrow x^3+8-x^3+9x=26\)
\(\Leftrightarrow9x=18\)
\(\Leftrightarrow x=2\)
\(\left(x+2\right)\left(x^2-2x+4\right)-x\left(x-3\right)\left(x+3\right)=26\)
\(\Leftrightarrow x^3+2^3-x.\left(x^2-3^2\right)=26\)
\(\Leftrightarrow x^3+2^3-x^3+9x^2=26\)
\(\Leftrightarrow8+9x=26\)
\(\Leftrightarrow9x=26-8\)
\(\Leftrightarrow9x=18\)
\(\Leftrightarrow x=18:9\)
\(\Leftrightarrow x=2\)